EXPLORING PARENTING APPROACHES FOR THE DESIGN OF FAMILY-BASED LEARNING MATERIALS TO PROMOTE PERSONAL SAFETY SKILLS IN CHILDREN WITH SPECIAL NEEDS - Oumpiam, Muthita; Amornpaisarnloet, Watinee (Journal of Education and Innovation, 2026)
This study aimed to 1) analyze parents’ experiences in teaching personal safety skills to children with special needs under their care, and 2) propose guidelines for designing learning media to support parents in promoting personal safety skills for upper elementary school children with special needs within the family context. The research employed the stages of understanding the target users and defining the problem, which are key components of the design thinking process. Six parents were purposively selected as key participant. Data were collected via in-depth interviews with parents and analyzed using content analysis. The findings revealed five key themes are 1) children’s readiness and limitations 2) perceived safety risks 3) parents’ experiences and strategies in teaching personal safety skills 4) challenges and barriers, and 5) parents’ needs and recommendations for supportive learning materials. Parents recognized developmental gaps and limitations in their children, which led them to integrate personal safety instruction into daily routines rather than providing explicit, in-depth teaching. At the same time, parents faced several challenges, including children’s individual limitations, lack of confidence in their instructional role, discomfort in discussing sexuality-related topics, and a shortage of appropriate learning materials. Synthesizing parents’ experiences with relevant literature suggests that learning media should enhance both parents’ knowledge and confidence. The content on personal safety skills should be presented through real-life situations to ensure relevance and applicability. Furthermore, the format of the learning media should allow learners to engage through multiple sensory channels to support learning that aligns with individual needs.